An analysis on the efficiency of Philippine microfinance institutions: A stochastic frontier approach - Dio, Ryan Lou (Animo Repository, 2023)
The creation of Microfinance Institutions (MFIs) is the government’s response to the market failure formed by commercial banks since the latter cannot accommodate the needs of low-income earners due to the high costs attached to it. However, numerous studies have claimed the existence of mission drifting, where MFIs are becoming more profit-oriented rather than focusing on social objectives. As a result, this paper estimates the financial and social efficiency of MFIs using a two-step Stochastic Frontier Approach from 2005 to 2018. Findings have shown that MFIs are primarily financially efficient yet socially inefficient. Also, the study determined a tradeoff between financial and social efficiency. MFIs focusing on financial efficiency face a much more significant social efficiency loss than those favoring the latter. Finally, NGO MFIs prioritize social efficiency, while non-NGO MFIs push for financial efficiency. Therefore, mission drifting exists in the Philippine MFI industry, where the financial efficiency of individual MFIs grows but at the expense of their social efficiency. MFIs are becoming profit-oriented pseudo-banks instead of fulfilling their social mission of helping the poor. They are becoming more financially motivated rather than promoting public welfare. However, not all hope is gone, as NGO MFIs have effectively prioritized social efficiency. Thus, policymakers should support the growth of the MFI industry, focusing on finding the balance between financial and social efficiency with the performance of MFI NGOs as the benchmark.